2003
DOI: 10.2472/jsms.52.12appendix_263
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Strength of Ti-6Al-4V Alloys Containing Small Artificial Defects

Abstract: The effects of small defects on the fatigue strength of Ti-6 Al-4V were investigated in tension-compression fatigue tests.specimens (Series A). Another series of specimens (Series B) were prepared to investigate the effect of a burr or a pre-crack which was introduced at the edge of the artificial hole. For Series A specimens, the fatigue limit was defined as the threshold for crack initiation from the edge of the hole. For Series B specimens, the fatigue limit was defined as the threshold for crack propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…8, the exponent representing the crack size dependence is likely to be close to 1/3 for the crack size regime l = 0.005-0.3 mm ( ffiffiffiffiffiffiffiffiffi ffi area p of 0.02-1 mm). Similar trends in crack size dependence have been confirmed for other materials (e.g., hard steels [43,44], low-carbon steels [41][42][43], titanium alloys [50], etc.). The value of DK th plateaus as the transition to the large crack regime is approached, where linear elastic fracture mechanics (LEFM) is applicable under a small scale yielding condition.…”
Section: 23supporting
confidence: 55%
See 1 more Smart Citation
“…8, the exponent representing the crack size dependence is likely to be close to 1/3 for the crack size regime l = 0.005-0.3 mm ( ffiffiffiffiffiffiffiffiffi ffi area p of 0.02-1 mm). Similar trends in crack size dependence have been confirmed for other materials (e.g., hard steels [43,44], low-carbon steels [41][42][43], titanium alloys [50], etc.). The value of DK th plateaus as the transition to the large crack regime is approached, where linear elastic fracture mechanics (LEFM) is applicable under a small scale yielding condition.…”
Section: 23supporting
confidence: 55%
“…Although the values for DK IIth and DK IIIth obtained in this study are dependent on the crack size and the crack-face interference, no significant difference between the tendencies of these values is observed, supporting the conclusion of Murakami et al Therefore, combining Eqs. (2)-(4), the threshold SIF ranges for mode II and III cracks are expressed by The three constants A, B and C can be determined by the least squares method using the data shown in Table 1 The crack size dependence of the fatigue limit associated with mode I fatigue cracks has been investigated by many researchers [23,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. For example, Frost [47] and Kobayashi and Nakazawa [49] proposed the following formula: r n w l ¼ constant, where r w is the fatigue limit of the material and l is the length of the twodimensional crack.…”
Section: 23mentioning
confidence: 99%
“…It has been reported that for various metallic materials, the fatigue limit as a crack‐growth threshold can accurately be predicted by the area parameter model . This model states that Δ Κ th at a stress ratio of −1 depends on the size of the initial crack or defect and the hardness of the material, expressed by the following equation: normalΔΚth=3.3×103()italicHV+120area1/3. The unit is MPa m for Δ Κ th .…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue strength of metallic materials is deteriorated by a variety of small defects, for example, non‐metallic inclusions, cavities, microstructural irregularities and cracks . Thus, the effect of small defects has been a major concern for fatigue researchers for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue strength of metallic materials is deteriorated by a variety of small defects, for example, non-metallic inclusions, 1-11 cavities, [12][13][14][15][16] microstructural irregularities 17,18 and cracks. [19][20][21] Thus, the effect of small defects has been a major concern for fatigue researchers for many years. In the 1980s, Murakami and Endo approached this problem in terms of fracture mechanics and proposed the ffiffiffiffiffiffiffiffi ffi area p parameter model that provides a quantitative estimation of the fatigue limit deteriorated by small defects.…”
Section: Introductionmentioning
confidence: 99%